2007
DOI: 10.1016/j.schres.2006.08.004
|View full text |Cite
|
Sign up to set email alerts
|

MRI abnormalities of the hippocampus and cavum septi pellucidi in females with schizotypal personality disorder

Abstract: Objective-This study examined MRI hippocampal volume and cavum septi pellucidi (CSP) in female subjects with schizotypal personality disorder (SPD) and comparison subjects.Method-MRI was performed on 20 SPD and 29 comparison subjects with delineation of left and right hippocampi. Number of slices containing the CSP was counted. Subjects were given a working memory task, the Delayed Alternation task and other measures of working memory including the Wechsler Memory Test-Revised and the California Verbal Learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 78 publications
5
33
0
1
Order By: Relevance
“…The same volume reduction has been observed in schizotypal disorders (Dickey et al, 2007). This is consistent with the hypothesis that hypercortisolism could result in hippocampal neurotoxicity in conditions such as bipolar disorder and schizophrenia.…”
Section: A3 Hippocampussupporting
confidence: 90%
“…The same volume reduction has been observed in schizotypal disorders (Dickey et al, 2007). This is consistent with the hypothesis that hypercortisolism could result in hippocampal neurotoxicity in conditions such as bipolar disorder and schizophrenia.…”
Section: A3 Hippocampussupporting
confidence: 90%
“…Earlier studies did not examine use of antipsychotics (DeLisi et al, 1993;Flashman et al, 2007;Jurjus et al, 1993;Kwon et al, 1998;Nopoulos et al, 1997;Rajarethinam et al, 2001;Shioiri et al, 1996). As these drugs may influence measures of CSP and may influence morphological alterations in brain regions related to CSP (Dickey et al, 2007;Chakos et al, 2005;McClure et al, 2006;Girgis et al, 2006), we examined the pattern of use of antipsychotics between groups. Fukuzako et al (1996) found that higher doses of neuroleptics were used in patients of schizophrenia who had CSP.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with schizophrenia patients and their relatives also suggest reduced medial temporal volume including the amygdala and/or hippocampal complex, but these findings have not been consistently observed in SPD (Dickey et al 2002a;Dickey et al 1999;Seidman et al 2002;Seidman et al 2003). One recent study reported reduced hippocampal volume in SPD (Dickey et al 2007). Taken together, these findings are consistent with a model of common temporal lobe abnormalities across the schizophrenia spectrum.…”
Section: Introductionmentioning
confidence: 88%